Contrasting changes in space use induced by climate change in two Arctic marine mammal species. (29th March 2019) - Hamilton, Charmain D.; Vacquié-Garcia, Jade; Kovacs, Kit M.; Ims, Rolf A.; Kohler, Jack; Lydersen, Christian
Abstract : Global warming is inducing major environmental changes in the Arctic. These changes will differentially affect species owing to differences in climate sensitivity and behavioural plasticity. Arctic endemic marine mammals are expected to be impacted significantly by ongoing changes in their key habitats owing to their long life cycles and dependence on ice. Herein, unique biotelemetry datasets for ringed seals (RS; Pusa hispida ) and white whales (WW; Delphinapterus leucas ) from Svalbard, Norway, spanning two decades (1995–2016) are used to investigate how these species have responded to reduced sea-ice cover and increased Atlantic water influxes. Tidal glacier fronts were traditionally important foraging areas for both species. Following a period with dramatic environmental change, RS now spend significantly more time near tidal glaciers, where Arctic prey presumably still concentrate. Conversely, WW spend significantly less time near tidal glacier fronts and display spatial patterns that suggest that they are foraging on Atlantic fishes that are new to the region. Differences in levels of dietary specialization and overall behavioural plasticity are likely reasons for similar environmental pressures affecting these species differently. Climate change adjustments through behavioural plasticity will be vital for species survival in the Arctic, given the rapidity of change and limited dispersal options.